Accountability of the Use of Regional Original Income and General Allocation Funds for Capital Expenditures of Regency and City Governments in The Province of East Java - Lasiyono, Untung; Putri, Junnia Pramesthia (Archives of Business Research, 2023)
This study aims to determine accountability management regional original income and general allocation funds for regional government capital spending Regencies and Cities in the Province of East Java. The type of this research is quantitative research using data quantitative tested and analyzed for furthermore get description management income original area and allocation funds general for capital spending. The data used in this study is data that is secondary, namely allocation general, income original area, allocation fund general and regional government capital spending Regencies and Cities in the Province of East Java in 2016-2020. This data collection technique uses documentation taken from the official website Ministry of Finance. Variable study among them that is management independent variable regional original income (X1) and general allocation funds (X2) as well dependent variable capital expenditure (Y). The population in this study is the report on the realization of the budget income and expenditures there are 38 regencies and cities in the East Java Province during 2016-2020 and the sample in this study is 20 regencies and cities in East Java Province, which consists of 15 regencies and 5 cities. Data analysis technique used in study this is analysis multiple linear regression. From the results data collection that has been done analysis show that: Management regional original income and general allocation fund are proven accountable used for capital expenditures for Regency and City Regional Governments in the East Java Province.